An approach for remote landslide mapping, South Nahanni Watershed, Northwest Territories, Canada. - Jermyn, Courtney E. (Author); Menounos, Brian (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2011)
This thesis presents two cost-effective techniques for landslide mapping in large, remote regions. The first technique uses ASTER satellite imagery to characterize and determine landslide distribution for part of the South Nahanni watershed. Results obtained from this study confirm that ASTER images are suitable for regional-scale landslide mapping. The second technique involved the creation of landslide susceptibility models for debris flow and rock/debris slides using logistic regression analysis. Cross validation confirmed the models' success. The debris flow model performed best whereas the rock/debris slide model was only moderately successful. Taken together, the two methods developed in this thesis provide a means to conduct a preliminary landslide investigation in large, remote regions or in developing countries where data are limited or site investigation is not possible. Maps produced from this analysis can be used to gain information on areas susceptible to landslides and to target key areas remotely before conducting field investigations. --P. ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1754770